A Holocene palaeomagnetic secular variation record from Lake Pupuke, New Zealand. Issue 4 (2nd October 2022) - Corkill, Ruth M.; Turner, Gillian M.
ABSTRACT: Palaeomagnetic records from three cores of lake sediment have been merged, producing a new Holocene geomagnetic secular variation record for northern New Zealand. The cores are from Lake Pupuke, a maar lake in Auckland Volcanic Field (AVF). They contain tephra from Rangitoto Volcano (530 ± 10 yr BP), Taupō (1718 ± 10 yr BP), Tūhua/Mayor Island (7637 ± 100 yr BP) and Rotomā tephra from Ōkataina Volcanic Centre (9423 ± 120 yr BP). These tephra dates are supplemented by selected radiocarbon age estimates. The cores were correlated using tephra and fine-scale variations in magnetic susceptibility. The natural remanent magnetisation is strong, stable and carried by fine-grained titanomagnetite from AVF's basaltic volcanoes. The resulting palaeosecular variation (PSV) record spans from 10, 000 to 1500 yr BP. It shows well-defined, millennial-scale swings in direction between 10, 000 and 8000 yr BP and between 4000 and 1500 yr BP, while between 8000 and 4000 yr BP variations are of higher frequency and lower amplitude and centre on the geocentric axial dipole field direction. This is in excellent agreement with published PSV records from Mavora Lakes, 1000 km further south, indicating the regional nature of PSV – resulting from broad-scale changes in the circulation of conducting iron-rich fluid of Earth's outer core.